PERAN GURU DAN PARTISIPASI SISWA MELALUI PEMBUATAN ECOBRICK PADA PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Saudah; Mukodi; Urip Tisngati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of teachers and student participation in ecobrick making activities within the Project to Strengthen the Profile of Pancasila Students at the elementary school level. The research employed a descriptive qualitative method, involving one homeroom teacher and twelve third-grade students selected through purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, as well as using Atlas.ti9 software through the stages of data input, coding, exploration, visualization, and data presentation. The results of the study show that: (1) Teachers play a significant role as communicators, facilitators, and demonstrators in ecobrick-making activities; (2) Students demonstrate active participation and enthusiasm during the activities; (3) Ecobrick-making contributes positively to shaping student character in accordance with the values of the Pancasila Student Profile, particularly in terms of environmental awareness and waste management. The optimal role of the teacher and the active participation of students in ecobrick- making activities make a tangible contribution to strengthening the character values of the Pancasila Student Profile at the elementary school level.